An Autoethnographic Reflection of Adult Learning and Paternal Grief. Issue 2 (May 2022) - Carpenter, Rob E.
This study examined my experience as a doctoral student following the death of my son. The focus of this research is on the interaction of paternal grief and adult learning in the context of higher education. The central emphasis seeks to offer existential bearing to the interplay between the narrative identities of adult learner and paternal griever that is seldom considered in combination for adult learning scholarship. I employed the reflexive process of autoethnography through free writing and review of personal journals. I used the analytical lens of a dialogical narrator who held two opposing I-positions of the self, adult learner and grieving father. This methodological approach allowed the pursuit of adult learning to emerge into a position that promoted reorganization of my grief, bridging the divergence of loss and gain. This study placed focus on the dialogical I-positions of self as a vector for growth. The novelty of this research is the placement of andragogical considerations in adult learning following paternal grief. These considerations have capacity to endorse the paternal griever I-position to begin understanding grief transition through pursuit of knowledge. Characterizing the embodied transition is central to the bereavement process. Bringing the transition into dialogue with adult learning can provide educators with enhanced instructional precision when planning and conducting learning activities in a grief environment.